Postoperative pancreatic fistula: Microbial growth determines outcome - Loos, Martin; Strobel, Oliver; Legominski, Matthias; Dietrich, Maximilian; Hinz, Ulf; Brenner, Thorsten; Heininger, Alexandra; Weigand, Markus A.; Büchler, Markus W.; Hackert, Thilo (Surgery, 2018)
Background - Postoperative pancreatic fistula is a dangerous complication in pancreatic surgery. This study assessed the impact of microbiologic pathogens detected in postoperative pancreatic fistula on clinical outcomes after partial pancreatoduodenectomy and distal pancreatectomy. - Methods - Microorganisms in postoperative pancreatic fistula were identified by microbiologic analyses from abdominal drains or intraoperative swabs during relaparotomy. Demographic, operative, and microbiologic data, as well as postoperative outcomes were examined. - Results - Of 2,752 patients undergoing partial pancreatoduodenectomy and distal pancreatectomy, 256 patients with clinically relevant postoperative pancreatic fistula (International Study Group of Pancreatic Surgery [ISGPS] grades B and C) were identified (9.3%) and microbiologic cultures were positive in 210 patients (82.0%), with a higher rate after partial pancreatoduodenectomy (95.8%) than after distal pancreatectomy (64.3%; P < .001). Microbiologic spectra differed distinctively between partial pancreatoduodenectomy and distal pancreatectomy. Detection of microorganisms in postoperative pancreatic fistula resulted in a higher morbidity and mortality, including postpancreatectomy hemorrhage (42.4% vs 21.7%; P=.009), sepsis (38.1% vs 6.5%; P < .001), wound infection (30.0% vs 6.5%; P=.001), reoperation (48.1% vs 10.9%; P < .001), hospital stay (median 42 vs 26 days; P < .001), and overall 90-day mortality (19.5% vs 4.3%; P=.013) and was identified as an independent risk factor for sepsis, wound infection, and reoperation in the multivariate analysis. - Conclusion - Detection of microorganisms in postoperative pancreatic fistula is frequent after pancreatic resection and indicates a turning point in the development of postoperative pancreatic fistula into a life-threatening condition. Whether early anti-infective therapy in combination with interventional measures or a surgical reintervention are warranted, has yet to be elucidated.
Available online 11 September 2018
Gesehen am 08.07.2019